Ответ:
Объяснение:
a)x³*(x²)⁵ =x³*=
б)(a²)³*(a⁴)² =
в)(a³)²*a⁵ =
г)(x²)⁵*(x⁵)² =
д)(m²m³)⁴ =
е)(x⁴x)²=
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
a)x³*(x²)⁵ =x³*
=![x^{13} x^{13}](https://tex.z-dn.net/?f=x%5E%7B13%7D)
б)(a²)³*(a⁴)² =![a^{6}*a^{8}= a^{14} a^{6}*a^{8}= a^{14}](https://tex.z-dn.net/?f=a%5E%7B6%7D%2Aa%5E%7B8%7D%3D%20a%5E%7B14%7D)
в)(a³)²*a⁵ =![a^{6}*a^{5}= a^{11} a^{6}*a^{5}= a^{11}](https://tex.z-dn.net/?f=a%5E%7B6%7D%2Aa%5E%7B5%7D%3D%20a%5E%7B11%7D)
г)(x²)⁵*(x⁵)² =![x^{10} *x^{10}=x^{20} x^{10} *x^{10}=x^{20}](https://tex.z-dn.net/?f=x%5E%7B10%7D%20%2Ax%5E%7B10%7D%3Dx%5E%7B20%7D)
д)(m²m³)⁴ =![(m^{5} )^{4}=m^{20} (m^{5} )^{4}=m^{20}](https://tex.z-dn.net/?f=%28m%5E%7B5%7D%20%29%5E%7B4%7D%3Dm%5E%7B20%7D)
е)(x⁴x)²=![(x^{5} )^{2}=x^{10} (x^{5} )^{2}=x^{10}](https://tex.z-dn.net/?f=%28x%5E%7B5%7D%20%29%5E%7B2%7D%3Dx%5E%7B10%7D)